Social Function of Irony in The Decameron by Giovanni Boccaccio - Delgado Del Águila, Jesús Miguel (2022)
Decameron has caused a convulsive reaction due to its social content and the mockery of patterns ascribed to medieval religion and morality in Italy. Therefore, support is provided here for the reasons leading to such astonishment about the literary work by Giovanni Boccaccio. Attention is given to the concept of the social function of irony, which in turn would start from three basic principles developed by Bergson. A comic situation requires intelligence, insensitivity and social criticism. Thus, it is possible to explain that the notion of irony is conditioned by the author’s worldview.